2013
DOI: 10.1575/1912/5711
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of thiols in the northwest Atlantic Ocean

Abstract: Thiol substances can form stable complexes with metals (especially copper and mercury) in the surface ocean that can impact cycling and bioavailability of those elements. In this study, I present seven concentration profiles of cysteine and glutathione, two low-molecular weight thiols, from the coastal northwest Atlantic Ocean and the Bermuda Atlantic Time Series (BATS) sampling site in the Sargasso Sea, a first for these regions. These two thiols were found in the upper 200 meters of the ocean at all sites, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 73 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…In estuarine, coastal and open ocean waters, their concentrations typically fall in the low nM range. Cys concentrations in the marine environments are typically lower, for instance 0.3 to 2.11 nM in the North Pacific (Dupont et al, 2006) and < 0.1 to 1.5 nM in the North Atlantic (Kading, 2013; Swarr et al, 2016). These Cys concentrations are about 2 orders of magnitude lower than those (> 100 nM) that reduced MeHg uptake in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In estuarine, coastal and open ocean waters, their concentrations typically fall in the low nM range. Cys concentrations in the marine environments are typically lower, for instance 0.3 to 2.11 nM in the North Pacific (Dupont et al, 2006) and < 0.1 to 1.5 nM in the North Atlantic (Kading, 2013; Swarr et al, 2016). These Cys concentrations are about 2 orders of magnitude lower than those (> 100 nM) that reduced MeHg uptake in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Cys, our study showed that MeHg uptake was decreased by 30% in the presence of 10 nM of GSH, a concentration approaching levels observed in marine environments, especially estuarine and coastal waters. Reported concentrations of GSH ranged from < 1 to 15 nM in the North-East Atlantic (Le Gall and van den Berg, 1998), 0.7 to 3.6 nM in coastal England (Al-Farawati and van den Berg, 2001), < 0.1 to 2.21 nM in the North Atlantic (Kading, 2013; Swarr et al, 2016), 0.01 to 0.76 in the North Pacific (Dupont et al, 2006), 0.23 to 6.23 nM in Galveston Bay, Texas (Tang et al, 2000), 0.17 to 0.79 nM in San Diego Bay, California (Tang et al, 2004), 0.08 to 0.13 nM in Cape Gear Estuary, North Carolina (Tang et al, 2004), and 0.37 to 0.45 nM in Norfolk Estuary, Virginia (Tang et al, 2004); however electro-analytical methods used in some of these studies may lead to over-estimates of GSH concentrations due to indiscriminate quantification (the authors assumed GSH was the primary component in total thiols). Notably, rather than GSH, γEC (γ-glutamylcysteine, a precursor of GSH) was found to be the most abundant thiol species (2 to 15 nM) in the North Pacific (Dupont et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Before analysis, frozen seawater samples were thawed overnight in a refrigerator and acidified to 15 mM with methanesulfonic acid (MSA). Samples (50 mL) were derivatized and analyzed according to the methods of Tang and colleagues (2003) with a few modifications (Kading, 2013). Changes to the Tang protocol included use of tris(2-carboxyethyl)phosphine (TCEP) as the reducing agent, and addition of the reducing agent after neutralization, rather than before.…”
Section: Derivitizationmentioning
confidence: 99%
“…As the primary source of thiols is biogenic production, co-variation between dissolved thiols and chlorophyll a (Chl a) concentrations might be expected and indeed has been observed in the surface coastal ocean (Al-Farawati and van den Berg, 2001). However, thiol concentrations were unrelated to Chl a in surface water from both the northwest Pacific and 4 northwest Atlantic (Dupont et al, 2006;Kading, 2013), which suggests that the sinks (primarily photo-oxidation and biological uptake) for thiols may be just as influential as biogenic production in determining ambient concentrations, especially in oligotrophic surface waters and at depths below the photic zone. For example, photochemical destruction of the thiol pool in the surface ocean has been demonstrated to be on the order of hours (Flock et al, 1997;Winterbourn and Metodiewa, 1999;Laglera and van den Berg, 2006;Moingt et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…The potential for stimulation of methylation in natural systems by thiol availability has not been investigated, but may be limited in oxic marine waters. Thiol mediated enhancement or suppression of Hg(II) uptake is specific to reduced species [Schaefer and Morel, 2009; and thiols found in marine waters may be oxidized in its primary role as a copper-binding ligand in low Hg marine waters [Kading, 2013]. Although previous measurements of dissolved thiols in marine waters have found that up to half may persist in their reduced forms [Dupont et al, 2006], distributions of small thiols such as cysteine and glutathione are found at nanomolar concentrations in the surface ocean, with depletion at depth [Kading, 2013;Swarr et al, 2012].…”
Section: Temporal Trends In Dissolved Mercury Speciationmentioning
confidence: 99%